The Urgency of the Threefold Relationship (With Allah, With Humans, and With Nature) in Environmental Fiqh to Address Contemporary Ecological Challenges - Achmad Rasyid Ridha; Misbahuddin M; Muhammad Suhufi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This research discusses Tri Hablum as the key to ecological balance. The method used in is research is the library metdod. Religion and ecology are things that cannot be separated. Likewise with Allah, humans and the universe where all three have a relationship with humans, Islam is a major religion in Indonesia, but when religious people are involved in it, at that time environmental pollution and environmental damage also occur. There is a paradigm shift from anthropocentric to anthropocosmic. This earth has been over-explored, because this earth is considered an object that needs to be explored. Nature was once sacred, but slowly over time it has experienced a desacralization, nature is no longer sacred so it has been over-explored. To overcome this, the role of humans is very urgent in realizing ecological balance.